Chondrocyte-peripheral blood mononuclear cell interactions: the role of ICAM-1. - Horner, A (1995)
Chondrocytes express a number of cell-surface molecules that mediate cell-cell or cell-matrix interactions. The expression of intercellular adhesion molecule-1 (ICAM-1) by chondrocytes under inflammatory conditions has been well documented. Here we demonstrate the involvement of ICAM-1-, CD18- and RGD-dependent adhesion mechanisms in chondrocyte-T-cell adhesion and in cell-mediated killing of chondrocytes in vitro. In the absence of cytokine stimulation, chondrocyte-peripheral blood mononuclear cell (PBMC) interactions were unaffected by inhibition of ICAM-1-dependent pathways but were significantly reduced by blockade of CD18- and RGD-dependent pathways. Following cytokine stimulation chondrocyte-PBMC adhesion and chondrocyte killing were significantly increased. These effects could be inhibited by the blockade of ICAM-1.